Biologically Inspired Cognitive Architectures (BICA) for Young Scientists Proceedings of the First International Early Research Career Enhancement School on BICA and Cybersecurity (FIERCES 2017) (Advances in Intelligent Systems and Computing,, 2018)
This book includes papers from the second year of the prestigious First International Early Research Career Enhancement School (FIERCES) series: a successful, new format that puts a school in direct connection with a conference and a social program, all dedicated to young scientists. Reflecting the friendly, social atmosphere of excitement and opportunity, the papers represent a good mixture of cutting-edge research focused on advances towards the most inspiring challenges of our time and first ambitious attempts at major challenges by as yet unknown, talented young scientists. In this second year of FIERCES, the BICA Challenge (to replicate all the essential aspects of the human mind in the digital environment) meets the Cybersecurity Challenge (to protect all the essential assets of the human mind in the digital environment), which is equally important in our age. As a result, the book fosters lively discussions on today's hot topics in science and technology, and stimulates the emergence of new cross-disciplinary, cross-generation and cross-cultural collaboration. FIERCES 2017, or the First International Early Research Career Enhancement School on Biologically Inspired Cognitive Architectures and Cybersecurity, was held on August 1-5 at the Baltschug Kempinski in Moscow, Russia.